2019
DOI: 10.1039/c9sc02544h
|View full text |Cite
|
Sign up to set email alerts
|

Mild synthesis of diboryldiborenes by diboration of B–B triple bonds

Abstract: A set of diboryldiborenes are prepared by the mild, catalyst-free, room-temperature diboration of the B–B triple bonds of doubly base-stabilized diborynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
0
21
0
3
Order By: Relevance
“…[43] One of the more promising synthetic methods to electron precise species thus far has involved diboration or hydroboration of diborenes, or diborynes, as demonstrated by Braunschweig and Kinjo. [44][45][46] Very recently, Braunschweig et al reported a remarkable cationic planar tetraborane with a hydrogen atom bridging the central B 2 entity (Scheme 5) exhibiting characteristics of a protonated diborene and a nonclassical three-center-two-electron B-H-B bond. [46,47] Scheme 5.…”
Section: With a Chain Structurementioning
confidence: 99%
See 1 more Smart Citation
“…[43] One of the more promising synthetic methods to electron precise species thus far has involved diboration or hydroboration of diborenes, or diborynes, as demonstrated by Braunschweig and Kinjo. [44][45][46] Very recently, Braunschweig et al reported a remarkable cationic planar tetraborane with a hydrogen atom bridging the central B 2 entity (Scheme 5) exhibiting characteristics of a protonated diborene and a nonclassical three-center-two-electron B-H-B bond. [46,47] Scheme 5.…”
Section: With a Chain Structurementioning
confidence: 99%
“…[44][45][46] Very recently, Braunschweig et al reported a remarkable cationic planar tetraborane with a hydrogen atom bridging the central B 2 entity (Scheme 5) exhibiting characteristics of a protonated diborene and a nonclassical three-center-two-electron B-H-B bond. [46,47] Scheme 5. Syntheses of the first linear tetraborane cation by Braunschweig et al (R = Dip, Mes).…”
Section: With a Chain Structurementioning
confidence: 99%
“…Recent success in adding B-B and B-H bonds across boronboron triple bonds 32,34 led us to consider the hydrophosphination of diborynes. We chose the least sterically encumbered diboryne currently available, B 2 (SI Dep ) 2 (9, SI Dep ¼ 1,3-bis(2,6-diethylphenyl)imidazolin-2-ylidene), 28 in the hope that this would allow the approach of the relatively bulky substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas P-H bond activation at transition 25 and main-group 26 metal centres is well documented, to the best of our knowledge the sole reported example of hydrophosphination of a homonuclear double bond comprising elements other than carbon is the 2016 report by Wang and Wu of hydrophosphination of the N]N bond in azobenzene with diphenylphosphine oxide. 27 Recent studies in our laboratories have demonstrated the feasibility of adding H-H, 28,29 B-H, [30][31][32] B-B, 33,34 S-S 35,36 and Se-Se 35 bonds across boron-boron multiple bonds. In this work, we show that uncatalysed hydrophosphination of both diborenes and diborynes can be used as a mild, selective and catalyst-free route to construct B-P bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of boron–element compounds containing B−E multiple bonds is a challenging field of research . Currently, the chemistry of B−B double and triple bonds is in the focus of interest . In terms of B=E double bonds with elements of Group 14, compounds exhibiting a double bond between boron and carbon were reported more than thirty years ago by Berndt, Nöth and Paetzold et al.…”
Section: Methodsmentioning
confidence: 99%